Grenada's national strategy to strengthen trade-related capacity (The Government St. George'sGD, 2003)
Provides an economic and trade policy overview. Evaluates and prioritizes Grenda's trade-related capacity building needs for participation in the negotiations and in the implementation of trade commitments. Sets out the capacity building needs. Identifies needs specific to the individual areas of negotiation and implementation.
Keywords: TRADE